2020
DOI: 10.2147/jaa.s205709
|View full text |Cite
|
Sign up to set email alerts
|

<p>Idiopathic Angioedema: Current Challenges</p>

Abstract: The etiological diagnosis of isolated recurrent angioedema poses problems because it must often be done urgently. Angioedema secondary to nonspecific mast cell activation (MC-AE) is the most frequent form and is usually mild. Bradykinin mediated angioedema (BK-AE) is rarer but potentially fatal in the absence of the correct treatment. Few biological markers exist. The C1-inhibitor (C1-inh) functional assay can exclude AE due to C1-inh deficiency. Genetic diagnoses of hereditary AE due to abnormal C1-inh AE hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 77 publications
0
21
0
4
Order By: Relevance
“…Here, we reviewed the similarities and differences of the mechanisms and clinical expression of BK-AE and MCM-AE. Knowledge of these differences, together with differences in laboratory markers, which are reviewed elsewhere [ 82 ], can help to reduce the rates of misdiagnosis and delayed diagnosis.…”
Section: Conclusion Open Questions and The Need For Further Studiesmentioning
confidence: 99%
“…Here, we reviewed the similarities and differences of the mechanisms and clinical expression of BK-AE and MCM-AE. Knowledge of these differences, together with differences in laboratory markers, which are reviewed elsewhere [ 82 ], can help to reduce the rates of misdiagnosis and delayed diagnosis.…”
Section: Conclusion Open Questions and The Need For Further Studiesmentioning
confidence: 99%
“…Obecnie wyróżnia się 4 typy AAE oraz 7 typów HAE (tab. 1) [6,[10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Wprowadzenieunclassified
“…Although these skin conditions are usually self-limiting, mucocutaneous airway inflammation can be life-threatening in itself, or might contribute to anaphylactic shock [ 4 , 6 , 8 ]. Recent studies have reported that urticaria and angioedema are among the most common dermatological reasons patients are admitted to emergency rooms [ 1 , 2 , 9 , 10 ]. In emergency cases, airway patency must be ensured.…”
Section: Introductionmentioning
confidence: 99%